1999
DOI: 10.1046/j.1365-8711.1999.02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended X-ray emission from the BL Lac object PKS 0521-365

Abstract: The definitive version is available at www.blackwell-synergy.com. Copyright Blackwell Publishing DOI : 10.1046/j.1365-8711.1999.02353.xModels that seek to unify BL Lacs and low-power radio galaxies predict that the two types of object should show similar isotropically emitted X-ray emission. Testing this is usually limited by difficulties in separating strong X-ray emission from a BL Lac nucleus and surrounding low-surface brightness emission. In this paper we report ROSAT HRI observations of the z = 0.055 BL … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
(62 reference statements)
4
7
0
Order By: Relevance
“…), but still worse than the broken power law model. The broken power law model absorbed by the Galactic column provides the best fit to the present data, consistent with the results obtained by Einstein, EXOSAT (Pian et al 1996), ROSAT (Pian et al 1996;Hardcastle et al 1999), BeppoSAX .…”
Section: Eg J0530-3626 (Pks 0521-365)supporting
confidence: 91%
See 1 more Smart Citation
“…), but still worse than the broken power law model. The broken power law model absorbed by the Galactic column provides the best fit to the present data, consistent with the results obtained by Einstein, EXOSAT (Pian et al 1996), ROSAT (Pian et al 1996;Hardcastle et al 1999), BeppoSAX .…”
Section: Eg J0530-3626 (Pks 0521-365)supporting
confidence: 91%
“…Hardcastle et al (1999) and Birkinshaw et al (2002) reported also the presence of extended emission that can be fitted with thermal plasma model with kT = 1.6 keV and Z = 0.05. Given the size of the PSF of EPIC camera on board XMM-Newton (12 −15 HEW, see Jansen et al 2001), the above mentioned structures are not resolved.…”
Section: Eg J0530-3626 (Pks 0521-365)mentioning
confidence: 87%
“…4). The best‐fitting spectrum has a spectral index α= 0.34 ± 0.03 (corresponding to a photon index Γ=α+ 1 = 1.34), consistent with the spectral index found by Garilli & Maccagni (1990) using EXOSAT , but flatter than the value α= 0.93 ± 0.03 reported by Hardcastle et al (1999) based on the ROSAT Position Sensitive Proportional Counter (PSPC) data. The effects of pileup and inadequate calibration of the response matrix may cause a systematic error of about 0.1 on the measured power‐law index.…”
Section: Discussionsupporting
confidence: 80%
“…Wings on the point response function (PRF) of the X‐ray optics and detector used to observe a BL Lac are therefore likely to exceed the brightness of the extended emission. Nevertheless, Hardcastle, Worrall & Birkinshaw (1999), using the ROSAT High Resolution Imager (HRI), reported a halo of resolved emission around the AGN in the low‐redshift ( z = 0.055 34; Keel 1985) BL Lac PKS 0521−365. Although PKS 0521−365 had a low X‐ray flux during this observation, the halo was only detectable above the wings of the PRF of the HRI over a small range of angles.…”
Section: Introductionmentioning
confidence: 99%
“… A straightforward cooling‐flow model with density and temperature within a cooling radius of (Hardcastle et al 1999), fitted in combination with a point‐source, is too spiked for the radial profile of the counts. Solid curves show the modelled point‐like emission (narrow curve), cooling‐flow model (broader curve) and their sum.…”
Section: X‐rays From the Cluster And Corementioning
confidence: 99%